Landscape simplification reduces classical biological control and crop yield. Issue 2 (18th January 2018) - Grab, Heather; Danforth, Bryan; Poveda, Katja; Loeb, Greg
Abstract: Agricultural intensification resulting in the simplification of agricultural landscapes is known to negatively impact the delivery of key ecosystem services such as the biological control of crop pests. Both conservation and classical biological control may be influenced by the landscape context in which they are deployed; yet studies examining the role of landscape structure in the establishment and success of introduced natural enemies and their interactions with native communities are lacking. In this study, we investigated the relationship between landscape simplification, classical and conservation biological control services and importantly, the outcome of these interactions for crop yield. We showed that agricultural simplification at the landscape scale is associated with an overall reduction in parasitism rates of crop pests. Additionally, only introduced parasitoids were identified, and no native parasitoids were found in crop habitat, irrespective of agricultural landscape simplification. Pest densities in the crop were lower in landscapes with greater proportions of semi‐natural habitats. Furthermore, farms with less semi‐natural cover in the landscape and consequently, higher pest numbers, had lower yields than farms in less agriculturally dominated landscapes. Our study demonstrates the importance of landscape scale agricultural simplification in mediating the success of biological control programs and highlights the potential risks to native natural enemies in classical biological control programs against native insects. Our results represent an important contribution to an understanding of the landscape‐mediated impacts on crop yield that will be essential to implementing effective policies that simultaneously conserve biodiversity and ecosystem services.